Age at sexual initiation and factors associated with it among youths in North East Ethiopia - Mazengia, Fekadu; Worku, Alemayehu (The Ethiopian Journal of Health Development, 2016)
Abstract Background: For behavioral as well as physiological reasons, early sexual debut increases young peoples’ risk for infection with HIV and other STIs. Youths who begin sexual activity early are more likely to have high-risk sex or multiple sexual partners and are less likely to use condoms. It is crucial to understand the factors associated with early sexual initiation in a broader context for designing and implementing effective interventions targeting youth. Objective: The objective of the study was to determine the median age at first sexual intercourse and the associated factors of sexual initiation among rural and urban youths (age 15- 24 years). Methods: A comparative cross sectional study was conducted between, March 1 -15, 2008, in Dessie town and Dessie Zuria Woreda. To draw a total sample of size 1294 (647 urban and 647 rural), a multistage cluster sampling was used. Bivariate and multivariate analyses were employed. Moreover, Kaplan Meier survival analysis was used to estimate the probability of sexual initiation at various age stratified by residence and sex. Result: About half, 51.3% of the youths have ever had sex. Rural youths initiate sexual intercourse at lower age than their urban counterparts with mean (ï‚±SD) (16.49+2.11) for rural and (17.18+2.32) for urban youths. The median age at sexual debut was 16 years for rural and 17 years for urban. The hazard ratio for sexual imitation was significant (AHR [95% CI] =1.45 [1.19, 2.55]. Multivariate analysis showed that being female by gender (AOR [95% CI]=1.56 [1.11, 2.19]), chewing Khat (AOR [95% CI] = 2.05 [1.05, 3.96]), drinking alcohol (AOR [95% CI] = 2.16 [1.12, 4.18]), watching pornographic materials at age < 18 years (AOR [95% CI] = 24.13 [3.28, 177.80]) and being less connected with arents (AOR [95% CI] =2.30 [1.35, 3.91]) were associated with early sexual initiation. Conclusion and Recommendation: Early sexual initiation prevails more in rural than urban youths. Delaying sexual debut can be achieved through well designed sexual education programs at earlier life. Strengthening the norm of virginity should be advocated. Equally, ways to access condoms and other contraceptives especially to rural youths should be sought for those who already initiate sexual intercourse. [Ethiop. J. Health Dev. 2009;23(2):154-162]